Impact of Egyptian and CIS Long Staple Cotton Varieties on Yarn Tensile Properties at Ring and Compact Spinning Systems: Cotton Yarn Properties vs. Spinning Systems (Biological Sciences - PJSIR, 2010)
Compact spinning system has proved itself better as compared to ring spinning system in improving the strength related properties of the yarn at low twist and high spindle speeds. The present study was undertaken to optimize the application of best combination of twist multiplier and spindle speed of ring and compact spinning system to Egyptian and CIS cotton varieties. Cotton varieties, twist multiplier and spinning system were found to be highly significant while spindle speed and all the interactions remained non-significant related to the tensile properties (yarn lea strength, single yarn strength, RKM and elongation) of the cotton varieties.